The nature of the formation of surface micro-roughness in vibration finishing and grinding processing - Mitsyk, A.; Fedorovich, V. (Національний технічний університет "Харківський політехнічний інститут", 2022)
The main aspects related to the nature of the formation of surface micro-roughness during vibration finishing and grinding processing are given. It is indicated that the material removal from the surface of the part occurs as a result of the combined action of micro-cutting processes, chipping of metal particles during repeated deformation of the processed surface areas, their fatigue and destruction, the formation, destruction and removal of secondary structures, and adhesion phenomena. It is noted that the real surface after vibration treatment is a set of roughnesses of a certain size, shape and direction. It is defined that the micro-roughness of the surface of the part during vibration finishing and grinding is formed in the form of traces from numerous impacts of abrasive granules on the surface of the part. The largest value of the granule penetration into the processed surface is determined, that makes it possible to characterize the trace from plastic compression in the zone of collision between the granule and the part. The technique and study of the mechanism of formation of surface microroughness is considered. An expression is determined for the normal component of the impact force, which characterizes the main effect on the mechanism of micro-roughness formation. The value of penetration of the granule into the metal of the part is determined. The study showed that the surface micro-roughness during vibration treatment is formed by impacts of granules on the part at different meeting angles. The traces from action of straight and oblique impacts are established. The average height of micro-roughness is calculated. According to the hodographs, the normal velocities of abrasive granules and parts are determined. The average value of the angle of impact of the granules with the part at any point of the trajectory of their movement is also determined. It was revealed that the velocities of granules and parts change in magnitude and direction during one period of the reservoir oscillation, reaching their limiting values, which are proportional to the reservoir movement velocities. The degree of proportionality is expressed by the similarity coefficient for the granule and the part. The average similarity coefficient was also determined by the points of the hodograph. The average values of the movement velocities of the granule and the part in the reservoir are obtained. The minimum and maximum value of the granule penetration into the surface of the part is established. The formulas for the limiting values of the granule penetration depth are given, taking into account the coefficient of ellipticity. The results of calculations for determining the height of micro-roughness of the processed part surface are presented. A formula is obtained for determining the surface micro-roughness during vibration finishing and grinding processing.

Наведено основні аспекти щодо характеру утворення мікрошорсткості поверхні при вібраційній здоблювально-зачищувальній обробці. Вказано, що видалення матеріалу з поверхні деталі відбувається в результаті спільної дії процесів мікрорізання, викришування частинок металу при багаторазовому деформуванні ділянок оброблюваної поверхні, їх втоми та руйнування, утворення, руйнування та видалення вторинних структур, адгезійних явищ. Зазначено, що реальна поверхня після віброобробки є сукупністю шорсткостей певної величини, форми та напряму. Встановлено, що мікрошорсткість поверхні деталі при вібраційній оздоблювально-зачищувальній обробці утворюється у вигляді слідів від численних ударів абразивних гранул по поверхні деталі. Визначено найбільшу величину проникнення гранули в оброблювану поверхню, що дає можливість характеризувати слід від пластичного стиску в зоні зіткнення гранули та деталі. Розглянуто методику та досліджено механізм утворення мікрошорсткості поверхні. Визначено вираз для нормальної складової сили удару, що характеризує основний вплив на механізм утворення мікрошорсткості. Встановлено величину проникнення гранули у метал деталі. Дослідженнями встановлено, що мікрошорсткість поверхні при віброобробці утворена ударами гранул о деталь під різними кутами зустрічі. Визначено сліди від впливу прямого та косого ударів. Обчислена середня висота мікрошорсткості. За годографами встановлено нормальні швидкості абразивних гранул та деталей. Також визначено середнє значення кута зіткнення гранул з деталлю у будь-якій точці траєкторії їхнього руху. Виявлено, що швидкості гранул і деталей змінюються за величиною та напрямком протягом одного періоду коливання резервуара, досягаючи своїх граничних значень, які пропорційні швидкостям руху резервуара. Ступінь пропорційності виражена коефіцієнтом подібності для гранули та деталі. Також за точками годографа визначено усереднений коефіцієнт подібності. Отримано середні значення швидкостей руху гранули та деталі в резервуарі. Встановлено мінімальну та максимальну величину проникнення гранули в поверхню деталі. Наведено формули граничних значень глибини проникнення гранули з урахуванням коефіцієнта еліпсності. Наведено результати розрахунків для визначення висоти мікронерівності поверхні та оброблюваної деталі. Отримано формулу для визначення мікрошорсткості поверхні при вібраційній оздоблювально-зачищувальній обробці.
Характер утворення мікрошорсткості поверхні при вібраційній оздоблювально-зачищувальній обробці
Keywords: vibration treatment; abrasive granule; processed part; collision between granule and processed part; collision angle; surface micro-roughness; velocity hodographs; віброобробка; абразивна гранула; оброблювана деталь; співударяння гранули; кут співударяння; мікронерівність поверхн; годографи швидкостей